Mechanotransduction in Coronary Vein Graft Disease - Ruiter, Matthijs Steven; Pesce, Maurizio (Frontiers in Cardiovascular Medicine, 2018)
Autologous saphenous veins are the most commonly used conduits in revascularization of the ischemic heart by coronary artery bypass graft surgery, but are subject to vein graft failure. The current mini review aims to provide an overview of the role of mechanotransduction signalling underlying vein graft failure to further our understanding of the disease progression and to improve future clinical treatment. Firstly, limitation of damage during vein harvest and engraftment can improve outcome. In addition, cell cycle inhibition, stimulation of Nur77 and external grafting could form interesting therapeutic options. Moreover, the Hippo pathway, with the YAP/TAZ complex as the main effector, is emerging as an important node controlling conversion of mechanical signals into cellular responses. This includes endothelial cell inflammation, smooth muscle cell proliferation/migration, and monocyte attachment/infiltration. The combined effects of expression levels and nuclear/cytoplasmic translocation make YAP/TAZ interesting novel targets in the prevention and treatment of vein graft disease. Pharmacological, molecular and/or mechanical conditioning of saphenous vein segments between harvest and grafting may potentiate targeted and specific treatment to improve long-term outcome.